2019
DOI: 10.3164/jcbn.18-45
|View full text |Cite
|
Sign up to set email alerts
|

Fucoxanthin administration delays occurrence of tumors in xenograft mice by colonospheres, with an anti-tumor predictor of glycine

Abstract: Fucoxanthin and its major metabolite, fucoxanthinol, have potent anti-cancer properties in carcinogenic model mice and against cancer cells. Evidence has accumulated regarding the diagnostic potential of biological metabolites as invasive and non-invasive obtainable approaches. We recently demonstrated that glycine was an effective predictor of the suppression of sphere formation and epithelial mesenchymal transition by fucoxanthinol in human colorectal cancer stem-like spheroids (colonospheres) under normoxia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…In addition, Fx induced anchorage-dependent apoptosis in human colorectal cancer (CRC) cells through the suppression of integrin signals [129,130]. In animal models, Fx administration significantly suppressed tumor development in a xenograft model of colorectal cancer [127,131], decreased the number of colorectal polyps, and decreased colonic lesions compared to untreated control mice [132]. In addition, Fx administration resulted in significantly lower numbers of colorectal cancer stem cell-like cells, cancer-associated fibroblast-like, tumor-associated macrophage-like and dendritic cell-like cells in colonic mucosa compared to untreated control mice [132].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…In addition, Fx induced anchorage-dependent apoptosis in human colorectal cancer (CRC) cells through the suppression of integrin signals [129,130]. In animal models, Fx administration significantly suppressed tumor development in a xenograft model of colorectal cancer [127,131], decreased the number of colorectal polyps, and decreased colonic lesions compared to untreated control mice [132]. In addition, Fx administration resulted in significantly lower numbers of colorectal cancer stem cell-like cells, cancer-associated fibroblast-like, tumor-associated macrophage-like and dendritic cell-like cells in colonic mucosa compared to untreated control mice [132].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…According to Bahmad et al , these studies primarily relied on two main criteria in their assessment: average volume of the generated spheres (size) and the average number of sphere-forming units (SFU) ( 52 ). Although our study did not evaluate SFU, size of colonosphere represents the proliferation of cells in the tumor mass, the capability of adhesion, and the anoikis resistance (AR) ( 53 , 54 ). A study demonstrated that SOX9 silencing resulted in AR loss in HCT116 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, we have revealed that the administration of Fx and FxOH inhibited tumorigenesis in xenograft NOD/SCID and BALB/c mice, respectively, subcutaneously injected with CCSCs-like cells prepared from human CRC HT-29 cells. In addition, the administration of Fx to BALB/c mice significantly downregulated the cyclin D1 expression in the tumor [ 97 , 116 ]. Furthermore, we investigated the effect of Fx in a Apc Min/+ mouse model of human FAP.…”
Section: Cancer Preventive Effect Of Brown Algae and Fx In Crc Model Animalsmentioning
confidence: 99%